Oral Tradition of Dusun Bangko Community Merangin District Jambi Province - Janiko Janiko; Atmazaki Atmazaki; Novia Juita (International Journal of Educational Dynamics, 2020)
This study aims to describe the form, function and meaning of oral literary sayings that exist in the people of Dusun Bangko in Jambi Province. Theories used in this study are oral traditions, functions of oral traditions, oral literature, and folklore. This type of research is a qualitative research with a descriptive approach. Data collection techniques are interviews, observation, documentation, and questionnaire research questions. Data analysis techniques are data reduction, presenting data, and conclusions. Based on data obtained in the field, the forms of oral traditions that developed in Dusun Bangko are petatah petitih, seloko and rhymes. All three oral traditions were once developed. However, at this time the Seloko has begun to be rarely used. While rhymes and petatah petitih very much used by the community. The function of oral tradition is as a reference for oneself and society so that it does not deviate from ethics, morals, and religion. Another goal is to cultivate human morals be better in order to give meaning to life. Furthermore, as a guide for a better way of life future. The meaning of oral traditions that develop in the community is very much. For example the meaning when doing immoral acts is different from stealing and the delivery method is also different. His sayings lead to destruction if life is not in accordance with the demands of the Qur'an and the Sunnah of Prophet Muhammad SAW.